Resistance of Doubled Haploid Rice Lines with Green Super Rice Characters to Bacterial Leaf Blight - Siti Nurhidayah; Bambang Sapta Purwoko; Iswari Saraswati Dewi; Willy Bayuardi Suwarno; Iskandar Lubis; Siti Yuriyah (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo) is a significant disease attacking rice crops worldwide. This disease attacks at various stages of plant growth and causes significant yield loss. Breeding new varieties resistant to BLB is important to support sustainable agriculture in the future. This study aimed to identify new superior green super rice (GSR) lines resistant to BLB disease. The experiment evaluated the resistance of lowland rice lines obtained from anther culture using a factorial randomized complete block design. The 1st factor was genotype, consisting of 20 lines, 2 checks of commercial varieties (Inpari 42 Agritan GSR and Inpari 18), a resistant check (Conde), and a susceptible check (Taichung Native 1). The 2nd factor was BLB pathotypes (i.e., III, IV, and VIII). Quantitative data on disease severity and severity index were analyzed using analysis of variance and t-Dunnett test at 5% level. The results showed that the interaction between genotype and pathotype affected the disease severity and severity index in both growth phases. The tested lines exhibited varying resistance, from susceptible to resistant, to BLB. Four lines (SN 11, 13, 57, and 58) showed moderate to resistant criteria for BLB disease of 3 pathotypes in both growth phases. The selected lines can be used as a source of parents for breeders and candidates for new superior varieties with BLB resistance properties to support the reduction of synthetic chemical bactericide inputs and control BLB disease. However, further field evaluations are necessary to assess their performance.